Efficient frontiers and fiscal stability: An ex-ante and ex-post application to the Irish public finances - Kieran McQuinn; Maurice J. Roche (The Economic and Social Research Institute (ESRI), 2016)
Revenue from taxation has become more volatile after the global financial crisis. In this paper we provide a mean-variance analysis for key taxation components in the Irish fiscal accounts. This approach is a useful complement to the more standard measures of fiscal developments, which typically focus on aggregate public finance indicators. In an Irish context, the analysis reveals that for a given taxation return, sourcing an increased amount of revenue from direct as opposed to indirect sources of taxation post 2008 would have provided a more stable fiscal environment.
Keywords: E62; H30; H21; 330; Efficient frontier; fiscal; taxation